Comunidades indígenas de la provincia de Chimborazo, Ecuador: permanencia de la sombra del régimen de hacienda - Tuaza Castro, Luis Alberto (Pontificia Universidad Católica del Perú. Fondo Editorial, 2014)
This paper analyzes current indigenous politics, from an approachto the indigenous communities historical process in the area of Guamote Totorillas, Ecuador. It is argued that after the dissolution of the hacienda system new forms of indigenous leadership emerged. The pervasiveness of ancient forms of leadership stemming from the hacienda system, though, prevent communities efforts to achieve unity and the design of a long term political project.

Este ensayo analiza la actual situación política indígena, a parti rdel acercamiento al proceso histórico de las comunidades indígenasde la zona Totorillas del cantón Guamote, Ecuador. Se argumenta que, después de la disolución de la hacienda, emergieron nuevas formas de liderazgo indígena; sin embargo, señala la compleja pervivencia de las antiguas formas de liderazgo que imposibilita la unidad de las comunidades y la consecución de un proyecto político único de largo alcance.
Indigenous communities of the province of Chimborazo, Ecuador: permanence of the shadow of the hacienda regime
Keywords: Comunidades; Hacienda; Política y liderazgo; https://purl.org/pe-repo/ocde/ford#5.04.03